Mycorrhizae set the stage for plants to produce a higher production of biomolecules and stress-related metabolites: a sustainable alternative of agrochemicals to enhance the quality and yield of beetroot (Beta vulgaris L.) - Yadav, Vinod Kumar; Kumar, Deepesh; Jha, Radha Krishna; Bairwa, Rakesh Kumar; Singh, Rajan; Mishra, Gaurav; Singh, Jyoti Prakash; Kumar, Adarsh; Vinesh, Banoth; Jayaswall, Kuldip; Rai, Abhishek Kumar; Singh, Arvind Nath; et al. (Frontiers in Microbiology, 2023)
Population explosion, environmental deprivation, and industrial expansion led to an imbalanced agricultural system. Non-judicial uses of agrochemicals have brought about decreased agro-diversity, degraded agro-ecosystem, and increased the cost of farming. In this scenario, a sustainable agriculture system could play a crucial role, however, it needs rigorous study to understand the biological interfaces within agroecosystems. Among the various biological components with respect to agriculture, mycorrhizae could be the potential candidate. Most agricultural crops are symbiotic with Arbuscular mycorrhizal fungi (AMF). In the present study, beetroot has been taken to see the effect of different AMFs on various parameters such as morphological traits, biochemical attributes, and gene expression analysis (ALDH7B4 and ALDH3I1) in beetroot. The AMF Gm- Glomus mosseae, Al- Acaulo sporalaevis, GG-Gigaspora gigantean were taken as a treatment to see the effect on above mentioned parameters in beetroot. We observed that among all the possible combinations of mycorrhizae, Gm+ Al+ GG performed best, and Al alone treatment was found poor performer with respect to all the studied parameters. With this study, it is concluded that the more combination of the mycorrhizae, the better results will come. However, the phenomenon is depending on receptivity, infectivity, and past nutrient profile of the soil.